Harnessing the Potential of Halal Tourism: Strategies for Sustainable Economic Development in Central Java, Indonesia - Aniqoh, Nur Aini Fitriya Ardiani; Tayob, Shaheed (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This study explores strategies for leveraging halal tourism to promote sustainable economic development in Central Java, Indonesia. As a pilot province for halal tourism, Central Java offers a unique case within this growing market segment. Using qualitative methods, the research integrates primary data from stakeholder interviews with secondary data from local tourism records. The findings indicate that while the halal tourism sector in Central Java shows promise, there are significant opportunities for further development. Key strategies identified include segmenting tourist destinations into historical, nature, and cultural categories, and creating regional tourist routes to improve accessibility and enhance the visitor experience. This study stands out by linking halal tourism with sustainable economic growth, aligned with the G20 agenda, providing novel insights and practical recommendations for policymakers and industry stakeholders.